KEDUDUKAN UNDANG-UNDANG NOMOR 40 TAHUN 1999 TENTANG PERS TERHADAP SEORANG PERS YANG MELAKUKAN TINDAK PIDANA PENCEMARAN NAMA BAIK - Siagian, Matheus; Radisman Saragih; Armunanto Hutahaean (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Legislation regarding the press has been regulated in Law no. 40 of 1999. The Law on the Press regulates all activities, works and forms of accountability of the press. The purpose of this research is to find out the position of the press law, and to find out how the press is held accountable. This study uses a normative juridical writing methodology, namely research conducted by examining library materials or secondary data. In this case, based on laws, books, research results, doctrines, related newspapers related to this writing. The Press Law in its position can be linked as a public law because the Press Law is in accordance with the characteristics of public law. This paper shows whether the existence of a press law can be an exception to the liability of press crimes. The Press Law regulates the functions, roles, rights, obligations as well as how the responsibility for criminal acts is carried out by press activities. In this way, criminal liability is also regulated in the KHUP, so that in the form of accountability for criminal acts the press can be divided into editors, companies, as well as publishers and printers.